2023
DOI: 10.3389/fpubh.2023.1090051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the use of prenatal care services and the risk of preterm birth between pregnant women with disabilities and those without disabilities: A nationwide cohort study

Abstract: ObjectiveThe difficulties faced by pregnant women with disabilities in accessing health care may make them less likely to receive prenatal care. The aims of this study were to compare the number of prenatal services and the risk of preterm birth between pregnant women with and without disabilities.MethodsA total of 2999 pregnant women aged ≥20 years with birth records in 2011–2014 in Taiwan were enrolled. Data were obtained from the Registration File for Physical and Mental Disabilities and the National Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Women who receive ANC have better birth outcomes, complications can be identified earlier, and they are more likely to deliver at a facility with a skilled provider [ 20 ]. For example, a study in Taiwan found WWD used fewer ANC services and had higher risk of preterm birth [ 21 ]. Because of this, all women should have access to ANC, regardless of their disability status [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women who receive ANC have better birth outcomes, complications can be identified earlier, and they are more likely to deliver at a facility with a skilled provider [ 20 ]. For example, a study in Taiwan found WWD used fewer ANC services and had higher risk of preterm birth [ 21 ]. Because of this, all women should have access to ANC, regardless of their disability status [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggests that utilisation of perinatal care services in women with disabilities is significantly lower than women without disabilities. 25 Moreover, most of WWD deliver babies at home and receive care from traditional providers. 26 Furthermore, these women remain dependent on spouses, family members and relatives to access healthcare facilities and also face economic challenges to seek high-quality care.…”
Section: Introductionmentioning
confidence: 99%